Defense responses against the sorghum anthracnose pathogen in leaf blade and midrib tissue of johnsongrass and sorghum. (April 2019) - Ahn, Ezekiel; Prom, Louis K.; Odvody, Gary; Magill, Clint
Abstract: Three isolates of Colletotrichum sublineolum P. Henn were inoculated on leaf blades and midribs of twenty-six johnsongrass cultivars with two sorghum cultivars, BTx 623 and SC 748-5 by using an excised leaf method. Phenotypic host responses from no response to severe infection, were observed. Some johnsongrass cultivars and BTx 623 showed different responses between the two tissues. Expression of six defense response related genes were measured using Real-time qRT-PCR. Leaf blade and midrib showed different patterns in BTx 623 inoculated with C. sublineolum ; high expression of CHS8 and TLP were measured in midrib at 24 and 48 hpi respectively. Highlights: Some cultivars appeared to differ in symptoms on leaf blades and midribs in natural infections. The majority of the 26 cultivars tested showed little difference in the relative scores, but several were significant. Two johnsongrass and two sorghum inbreds were tested for defense response based on levels of mRNA for 6 genes. Sorghum BTx623 differed in both symptoms and induction of defense responses in the two tissues.